2013
DOI: 10.1128/mcb.01442-12
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Analysis of CLASP-Interacting Protein Functions during Interphase Microtubule Dynamics

Abstract: The microtubule (MT) plus-end tracking protein (؉TIP) CLASP mediates dynamic cellular behaviors and interacts with numerous cytoplasmic proteins. While the influence of some CLASP interactors on MT behavior is known, a comprehensive survey of the proteins in the CLASP interactome as MT regulators is missing. Ultimately, we are interested in understanding how CLASP collaborates with functionally linked proteins to regulate MT dynamics. Here, we utilize multiparametric analysis of time-lapse MT ؉TIP imaging data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
2
20
2
Order By: Relevance
“…Furthermore, indirect evidence suggests that Klar may also function in branch migration in trachea [261], in wing development [262], in the remodeling of neuroendocrine cell [263], and in starvation stress resistance [264]. Finally, in cultured cells, Klar suppresses microtubule shrinkage events and promotes microtubule stability [265]. Although the molecular mechanism by which Klar functions remains obscure, in many cases it has been proposed to somehow link cargoes (vesicles, nuclei, lipid droplets, RNP particles, chromosomes) to microtubules and/or microtubule motors.…”
Section: Components Of the Droplet Transport Machinerymentioning
confidence: 99%
“…Furthermore, indirect evidence suggests that Klar may also function in branch migration in trachea [261], in wing development [262], in the remodeling of neuroendocrine cell [263], and in starvation stress resistance [264]. Finally, in cultured cells, Klar suppresses microtubule shrinkage events and promotes microtubule stability [265]. Although the molecular mechanism by which Klar functions remains obscure, in many cases it has been proposed to somehow link cargoes (vesicles, nuclei, lipid droplets, RNP particles, chromosomes) to microtubules and/or microtubule motors.…”
Section: Components Of the Droplet Transport Machinerymentioning
confidence: 99%
“…Because of the density of microtubules in cells, microtubule dynamics can only be reliably measured in the cell periphery, which can bias measurements of microtubule dynamics and does not allow monitoring of microtubule behavior toward the center of the cell (27). To overcome this bias, recent studies have monitored microtubule dynamics by imaging fluorescently labeled microtubule plus-end tracking proteins, such as EB1ΔC (referred to throughout the manuscript as EB1, for simplicity) (27,28). Imaging of EB1-GFP fluorescence typically results in the observation of "comets," which reflects EB1-GFP binding to the rapidly growing plus ends of microtubule polymers.…”
Section: Nad + Prevents Microtubule Polymer Disassembly Elicited Bymentioning
confidence: 99%
“…36,40 Additional studies have shown that Drosophila CLASP interacts with ACF7 (Actin crosslinking family 7) 41 and in mammalian cells CLASP2 functions downstream of ACF7 during polarized cell migration. 35 CLASP2 also interacts with the Rac and Cdc42 effector IQGAP1, which has fundamental roles during cell-cell contact formation.…”
Section: Mt Plus-ends As Platforms For Protein Interactions At Ajsmentioning
confidence: 99%